TRANSFORMING HALAL AWARENESS: SYNERGY OF LIFESTYLE, DIGITAL LITERACY, AND IMPLICATIONS FOR THE HALAL ECONOMY - Prihandono, Agung; Lusianti, Dina; Yasin, Rozaq M; Ula, Ahmad Nilnal Munachifdlil (LPPM Universitas Jambi, 2026)
The rapid development of the halal industry requires a deeper understanding of factors can increase public awareness, trust, and attitudes towards halal products. This study aims to analyze the influence of lifestyle and digital literacy on halal awareness and its impact on individual beliefs and attitudes towards halal products using the theory of planned behavior approach. This study involved 300 respondents from Indonesia and Malaysia, who were selected using purposive sampling techniques, with the criteria of a Muslim sample who regularly buys and consumes chicken and actively seeks halal information through digital platforms. Data were collected using an online questionnaire and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) approach to test the relationships among variables. The results of the study show that lifestyle and digital literacy contribute positively to increasing halal awareness. Halal awareness has been proven to have a significant role in shaping trust and attitudes towards halal products. These findings confirm that increasing halal awareness can strengthen public acceptance of halal products and build consumer loyalty. The implications of this study highlight the importance of wider education and campaigns related to halal lifestyle and digital literacy to improve public understanding. Halal industry players are advised to strengthen product transparency, utilize digital technology in disseminating information, and collaborate with various parties, including the government and religious institutions, to create a stronger and more sustainable halal ecosystem. The findings of this study have significant implications for economic development, especially in the context of the halal industry and economic development based on Islamic values.